Low-Dose Everolimus Maintenance Therapy for Renal Angiomyolipoma Associated With Tuberous Sclerosis Complex - Luo, Cong; Ye, Wen-Rui; Zu, Xiong-Bin; Chen, Min-Feng; Qi, Lin; Li, Yang-Le; Cai, Yi (Frontiers in Medicine, 2021)
Objective: To assess the safety and efficacy of low-dose everolimus maintenance therapy for tuberous sclerosis complex-related renal angiomyolipoma (TSC-RAML) patients that had previously undergone standard-dose treatment for a minimum of 6 months. Materials and Methods: In total, 24 patients with a definitive TSC diagnosis were enrolled from April 2018 – April 2019 at Xiangya Hospital, Central South University. All patients underwent low-dose everolimus maintenance therapy following standard-dose everolimus induction therapy for a minimum of 6 months. Patients additionally underwent TSC1/TSC2 genetic testing, And they were followed-up at 3, 6, 12, 18, and 24 months. The Response Evaluation Criteria in Solid Tumors (RECIST, version 1.1) criteria were used to monitor patient RAML responses, while adverse events (AEs) were assessed as per the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE, version 4.0). P < 0.05 was the significance level for all analyses, which were performed using SPSS 19.0. Results: TSC1/TSC2 gene mutations were present in all 24 patients, all of whom achieved a significant reduction in TSC-RAML volume within the initial 6-month induction therapy period, and exhibited volume stabilization during the low-dose maintenance therapy treatment period without any instances of TSC-RAML regrowth. Adverse events (AEs) were significantly less severe and less frequent over the course of maintenance therapy relative to standard therapy. Conclusions: Low-dose everolimus maintenance therapy represents an effective approach to achieving TSC-RAML control following a minimum of 6 months of full-dose induction therapy, and may be associated with decreases in everolimus-related AE frequency and severity.